Effects of "living high-training low and high" on sleep, heart rate variability, and psychological responses in elite female cyclists - Pirlot, T.; Mihailovic, T.; Gimenez, P.; Millet, G. P.; Brocherie, F.; Fruchart, E.; Ravier, G.; Baron, B.; Bouzigon, R.; Guirronnet, S.; Brunet, E.; Groslamber, A. (European Journal of Sport Science, 2025)
"Living High-Training Low and High" (LHTLH) is an altitude/hypoxic training method used to improve physical performance at sea level. The aim of this exploratory study was to investigate the effects of LHTLH on sleep, heart rate variability (HRV), and psychological stress in 10 elite/international level female cyclists (mean age: 17.3 ± 1.2 years). Participants were monitored for 19 days divided into 3 periods: (i) normoxia (5 days preceding LHTLH), (ii) early acclimatization (day 1-4 of LHTLH), and (iii) middle acclimatization (day 5-14) performed in hypoxic rooms (FiO2 = 15.09%). Questionnaires of psychological stress and sleep disturbance, sleep architecture (determined through an electroencephalography sleep headband), and HRV (measured at rest with a chest strap) were recorded during the 3 periods. The results found that, compared to normoxia, there was no significant difference in total sleep time, sleep efficiency, latency, or waking during the early acclimatization period. However, a significant increase in sleep disturbance (2.5 ± 1.1 vs. 4.9 ± 2.5 a.u. and p < 0.001), alterations of HRV, and sleep architecture with a significant increase in stages 1 (21.8 ± 3 vs. 25.9 ± 3.6 min and p < 0.007) and 2 (201.2 ± 55 vs. 238.5 ± 55 min and p < 0.008) of sleep was observed. During the middle acclimatization period, the athletes had restorative sleep but HRV remained altered, with a significant increase in external tension (1.24 ± 0.4 vs. 2.83 ± 1.8 a.u. and p < 0.05). All these findings suggest that an acclimatization period of at least 4 days is required to recover restorative sleep during LHTLH intervention.